(2) + (2)
=> 8x - 6y = -46 ———(3)
(1) + (3)
=> 5x + 6y + (8x - 6y) = 20 - 46
=> 13x + (6-6)y = -26
=> 13x + 0y = -26
=> 13x = -26
=> x = -26/13
=> x = -2
=> 5(-2) + 6y = 20
=> 6y = 20 + 10
=> 6y = 30
=> y = 5
x = -2, y = 5 => C
This statment only works for linear systems because in non-linear systems it is okay to have more than one soultion
but if the system is linear than you can define it by it two soultions or in other words it takes two points to form a line and if two lines pass through the same points then you can define them by those point and they are the same line
Answer: the bottom one
Step-by-step explanation:
i think its the bottom one i did some math
B. 12 would be your answer
Answer: 3
Step-by-step explanation:
At first you would subtract 39 from 60. Then you would do 21/5.5 and you would get 3.818… and due to the fact you can't go over 60 you would round to 3 and not 4